1978
DOI: 10.1177/000456327801500115
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Induction by Drugs

Abstract: SUMMARY The properties of the hepatic microsomal, drug detoxicating, enzyme system are reviewed with particular reference to its inducibility. Induction is modified by various factors of which the diet is particularly important. A theoretical model system for induction has been proposed and this is discussed. There are a number of methods for assessing microsomal enzyme induction in man, none of which is ideal. Nevertheless, induction is a well recognised phenomenon in man and has a bearing on the metabolism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Thus, it seems that the decrease in ALT and AST activities enhanced the induction of microsomal drug-metabolizing enzymes, and these regulatory controls may act to conserve nutrients and energy for the cells. These results are in consonance with the studies of Orrhenuis et al (1965), Marshall (1978, Remmer and Merker (1993), and Singh et al (1998). The reports of these workers showed that increased protein synthesis due to increased glucuronidation of the endoplasmic reticulum and decreased permeability of the liver cells resulted in induction of the microsomal drugmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, it seems that the decrease in ALT and AST activities enhanced the induction of microsomal drug-metabolizing enzymes, and these regulatory controls may act to conserve nutrients and energy for the cells. These results are in consonance with the studies of Orrhenuis et al (1965), Marshall (1978, Remmer and Merker (1993), and Singh et al (1998). The reports of these workers showed that increased protein synthesis due to increased glucuronidation of the endoplasmic reticulum and decreased permeability of the liver cells resulted in induction of the microsomal drugmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 92%
“…The Protein/RNA ratios are suggestive of enzyme induction and serum endoplasmic reticulum proliferation (Marshall, 1978;Hunter and chasseaud, 1978;Bertolini et al, 1980;Salem et al, 1981;Bahtnager and Misra, 1988;Singh et al, 1998). This is because microsomal enzyme induction could most likely depends on de novo protein biosynthesis (Bertolini et al, 1980;Rodwell, 1996;Coon, 1996;Singh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, since we found essentially no metabolite 17 or 18 in serum, the differences between RIA and h.p.l.c. (Gelehrter, 1976;Marshall, 1978). The enhanced clearance of antipyrine in the healthy subjects is also consistent with enzyme induction, but does not prove that phenytoin increased cyclosporin metabolism in these individuals.…”
Section: Discussionmentioning
confidence: 86%
“…Other investigators have reported enhancement of the metabolism of quinidine and theophylline by phenytoin in patients aged 65 years (Urbano, 1983;Kroboth et al, 1983). Since phenytoin and rifampicin appear to be more powerful enzyme inducing agents than dichloralphenazone (Gelehrter, 1976;Marshall, 1978), it seemed possible that differences in the enzyme inducing drugs might explain the apparent discrepancy.…”
Section: Impaired Enzyme Induction By Rifampicin In the Elderlymentioning
confidence: 99%